Short Communication: The lifecycle of Neocaridina denticulata and N. palmata in aquariums - HANAN HASSAN ALSHEIKH MAHMOUD; MOH. HUSEIN SASTRANEGARA; Endang Srimurni K Kusmintarsih (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mahmoud HHA, Sastranegara MH, Kusmintarsih ES. 2020. Short Communication: The lifecycle of Neocaridina denticulata and N. palmata in aquariums. Biodiversitas 21: 2396-2402. The study on the life cycle of Neocaridina spp. is important because it plays a major role in the economy and trade between countries. However, there is a lack of sufficient studies on this particular topic. One of the factors that influence Neocaridina spp. life production is its life cycle and the associated water parameters. The objectives of this study were to conduct, observe, and record the life cycle of Neocaridina denticulata and N. palmata and the associated with water parameters (temperature, pH, ammonia, nitrite, and oxygen) in the aquarium. The results showed that there was no difference in the life cycle stages between the two shrimp species. Both species reached the first sexual maturity stage of the life cycle at 75 days, with the maximum body length of the mature shrimp ranging from 2.30-3.00 cm. The eggs became larvae in 15 days, larvae reached the juvenile stage after 60 days, and the juvenile became mature in 15 days. The number of eggs was influenced by the body size of the female shrimps; smaller females produced fewer eggs. Optimal water quality varies by species and must be monitored to ensure growth and survival. The temperature range in this study was 25-28°C and the pH was 6.5-8.0. The ammonia level was in the range between 1.21 and1.72 mg/L, the nitrate was between 0.06 and 7.91 mg/L, and the oxygen was around 5.5-7.9 mg/L. All of the water quality parameters in this study are within the acceptable range for Neocardina cultivation.